Revitalisasi Pengabdian Kepada Masyarakat Menghadapi Problematik Paradoks Globalisasi - Suhendra Yusuf (LPPM UNINUS, 2011)
Problematic life of the nation is becoming increasingly complex and chaotic. In many ways the problem is not only novel and divergent, but sometimes clashing with the occurence in the past. Of course it does not happen in our country only. Many countries around the world have experienced the same thing. In essence of education, we are strongly face a problematic paradox in the nature of globalization: From one point of view, we must build the quality of education in accordance with a reference quality (benchmarking) of global competence so that we would not be marginalized in competition between nations - on the other side of education we bound to consider the quality of education in diversity and local knowledge to enable students undergoing life on the earth we live. Therefore, the implementation of the Dharma community services should be adjusted to surmount problematic in such a very convoluted life.